Changes in psychological distress after first vaginal intercourse in late adolescence. (June 2021) - Vasilenko, Sara A.; Lefkowitz, Eva S.; Maggs, Jennifer L.
Abstract: Introduction: Although early sexual intercourse may be associated with increased depressive symptoms, little research has examined whether first intercourse in late adolescence is associated with changes in mental health. Methods: This paper uses 3 years of longitudinal data from previously sexually abstinent late adolescent students at a large state university in the northeastern United States ( N  = 144, 53.5% male, M age = 18.5 years old, 47.2% White, 26.4% Asian/Hawaiian/Pacific Islander, 20.1% Hispanic/Latino, 18.1% Black/African American) to examine whether levels of psychological distress changed after first intercourse. Results: Students' distress decreased after first intercourse, although this effect was only significant two or more semesters after first intercourse. There were no gender differences in these associations. Conclusions: Findings suggest first intercourse was, on average, associated with decreased psychological distress for both male and female late adolescents.